Numerical study on gap resonance coupled to vessel motions relevant to side-by-side offloading. (1st December 2021) - Ekerhovd, Ivan; Ong, Muk Chen; Taylor, Paul H.; Zhao, Wenhua
Abstract: Side-by-side offloading, where one vessel is moored parallel to and very close to a second vessel, is quite a common offshore operation. These side-by-side operations will not take place in severe sea states. However, at certain frequencies, even benign sea states may excite resonant fluid motions in the form of localised long waves with spatial variation only along the gap. For practical applications, the amplitude of the water surface motion in the narrow gap can be important by itself or due to coupling with vessel motions. To investigate the effect of vessel motions on gap resonance, a series of numerical simulations based on linear potential flow theory are conducted. The numerical model is validated against experimental data which have been made publicly available, allowing the viscous damping coefficient to be calibrated as well, at least at laboratory scale. The gap resonances are investigated for various configurations, e.g. fixed + fixed vessels, floating + fixed vessels and floating + floating vessels. The most striking observation is that the lowest or first gap resonant peak, which is obtained in the case of two fixed vessels, disappears completely when one of the two or both vessels are allowed to move freely. This loss of the first mode is caused by allowing relative sway between the two vessels, the effect of the release of the heave motion is smaller. Highlights: Gap resonance is investigated for two vessels in side-by-side operation. Numerical simulations are conducted based on potential flow theory. The vessels are floating + fixed vs fixed + fixed. Coupling of gap resonance and vessel motions is investigated in detail.